Legal challenges in protecting children against cyber bullying in Malaysia: an overview - Che Soh @ Yusoff, Roslina (Onikilevha Yayincilik A.S, 2019)
Cyber bullying, in its different forms, is common among children and adolescents and is facilitated by the increased use of technology. The consequences of cyber bullying could be severe, especially on mental health, potentially leading to suicide in extreme cases. Although parents, schools and online social networking sites are encouraged to provide a safe online environment, little is known about the legal avenues which could be utilised to prevent cyber bullying or act as a deterrent. This paper attempts to explore current laws, and the challenges that exist to establishing cyber bullying legislation in the context of Malaysia. It is arguable that a number of statutes may be of assistance in relation to cyber bullying, namely the Computer Crimes Act 1997, the Communication and Multimedia Act 1998, the Penal Code and the Child Act 2001, however, the implementation and usage of these legislations are still limited and there is a lack of awareness of cyber bullying in Malaysia. The current paper presents an evaluation of the legislative and public policy solutions to cyber bullying available in Malaysia, outlines the challenges and recommends some legal reforms in protecting the children against cyber bullying for their future well being. The paper employs doctrinal and statutory analysis.